The shaping of adolescent behaviour in the lights of Al-Bukhari's Ahadith : an applied study of International Islamic University Malaysia students' behaviour - Siti Samihah binti Mohd Yusoff (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, Internatinonal Islamic University Malaysia, 2016)
Adolescent behaviour is an important concern of the society. As university students are still in the stage of adolescence, this study attempts to discover the condition of students' behaviours. International Islamic University Malaysia (IIUM) is well known as a 'Garden of Knowledge and Virtue'. As students of an Islamic university, the students there are expected to have good behaviour and must manifest commendable behaviour in their lives. However, in reality, some of them do not manifest good behaviour and fail to behave according to the expected norms. This issue should not be taken lightly and underestimated. Thus, a research was conducted by using a questionnaire which was inspired by Al-Bukhari's aÍhadith related to behaviour towards Allah, others, and oneself. The respondents for this research consist of first year students enrolled in the Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) in their late adolescence with the age range of 20 to 21. A descriptive statistic method was used for all the collected data and the data were analysed and processed by using the software Statistical Package for Social Science (SPSS). The result shows that a majority of the respondents have good knowledge of the Sunnah of Prophet Muhammad. Overall, most of the respondents have good behaviour. However, some of the respondents confessed that they have bad behaviour such as loitering and spreading gossips. Even though the mean shown for bad behaviour is the lowest among other behaviours, this matter needs to be addressed. Indeed, the result shows that KIRKHS students have also done certain behaviours that are not expected. In a nutshell, there is a need to follow the Sunnah of Prophet Muhammad r because the best guidance is the guidance of Prophet Muhammad .